Altered relation of the renin-aldosterone system and vasoactive peptides in type 2 diabetes: The KORA F4 study. (September 2016) - Then, Cornelia; Rottenkolber, Marietta; Lechner, Andreas; Meisinger, Christa; Heier, Margit; Koenig, Wolfgang; Peters, Annette; Rathmann, Wolfgang; Bidlingmaier, Martin; Reincke, Martin; Seissler, Jochen
Abstract: Background and aims: The exact mechanism of premature atherosclerosis in diabetes is still unclear. Inappropriate activation of the renin-aldosterone-angiotensin system may be an important risk factor for cardiovascular disease. We investigated whether renin and aldosterone are associated with vasoactive peptides midregional-pro atrial natriuretic peptide (MR-proANP) and midregional-pro adrenomedullin (MR-proADM), or with intima media thickness (IMT) as a marker for early atherosclerotic alterations in the general community and in subjects with type 2 diabetes. Methods: In 1261 participants in the KORA F4 study, the associations of renin, aldosterone and aldosterone to renin ratio with MR-proANP, MR-proADM and IMT were assessed using linear regression models stratified for the presence of prediabetes and type 2 diabetes. Results: After adjustment for confounding factors, an inverse association of MR-proANP with renin ( p  = 0.002) and aldosterone ( p  = 0.021) and a direct association of MR-proADM with renin ( p  < 0.001) and aldosterone ( p  = 0.019) were seen in nondiabetic individuals. In diabetic subjects, there was no significant correlation of MR-proANP or MR-proADM with renin or aldosterone. Renin and aldosterone were not directly associated with IMT in non-diabetic subjects and the total cohort, whereas aldosterone was associated with IMT in diabetic participants ( p  = 0.005). Conclusions: This study shows associations between renin, aldosterone and MR-proANP/MR-proADM plasma levels that are altered in type 2 diabetes. Plasma renin and aldosterone are not independent biomarkers for early atherosclerotic damages of the carotid arteries in the general community. Highlights: Renin and aldosterone are inversely associated with midregional-pro atrial natriuretic peptide (MR-proANP). Renin and aldosterone are directly associated with midregional-pro adrenomedullin (MR-proADM). These associations are diminished or abolished in diabetic subjects. Renin and aldosterone are not directly associated with intima media thickness (IMT) in the general community. Aldosterone is directly associated with IMT in diabetic subjects.